The Role of Ethical Leadership Versus Institutional Constraints: A Simulation Study of Financial Misreporting by CEOs - Chen, Stephen (Journal of business ethics, 2010)
This article examines the proposition that a major cause of the major financial accounting scandals that received much publicity around the world was unethical leadership in the companies and compares the role of unethical leaders in a variety of scenarios. Through the use of computer simulation models, it shows how a combination of CEO's narcissism, financial incentive, shareholders' expectations and subordinate silence as well as CEO's dishonesty can do much to explain some of the findings highlighted in recent high profile financial accounting scandals. Furthermore, it shows that the nature and impact of ethical leadership depends greatly on the institutional setting and can be expected to vary greatly by country and culture. In certain circumstances ethical leadership can have either a negligible or even opposite effect to that expected.